The high temperature creep properties of a thermally sprayed CoNiCrAlY coating via small punch creep testing - Jackson, G.A.; Chen, H.; Sun, Wei; McCartney, D.G. (Trans Tech Publications, 2017)
Thermal barrier coatings (TBC’s) protect superalloy components from excessively high temperatures in gas turbines. TBC’s comprise of a ceramic top coat, a metallic bond coat and a thermally grown oxide (TGO). The creep behaviour of the MCrAlY bond coat, which is sensitive to the composition and the method of deposition, has a significant effect on the life of the TBC. High velocity oxy-fuel (HVOF) thermal spraying is a popular deposition method for MCrAlY bond coats however the creep properties of HVOF MCrAlY coatings are not well documented. The creep behaviour of a HVOF thermally sprayed CoNiCrAlY coating has been determined by small punch creep (SPC) testing. Tests were conducted between an equivalent uniaxial stress range of 37-80 MPa at 750 °C on two different SPC rigs and between 30-49 MPa at 850 °C on a single SPC rig. The measured steady-state creep deformation rates at 750 °C were consistent across the two rigs. A comparison with previous work demonstrated that the creep behaviour of HVOF CoNiCrAlY coatings is not sensitive to the manufacturing variability associated with HVOF thermal spraying. The CoNiCrAlY coating exhibited typical SPC deformation at 750 °C. At 850 °C the CoNiCrAlY coating showed significantly different creep behaviour which could be attributed to the onset of superplasticity.